Floristic Composition of Plankton in Shitalakhsya River, Narayanganj, Dhaka - Hossain Bhuiyan, Mohammad Azmal; Islam, Md Rasikul; Islam, Sam Shariar; Kowser , Abu; Khondker, Moniruzzaman (Dhaka University Journal of Biological Sciences, 2022)
Information of phytoplankton flora of polluted river ecosystems of Bangladesh are scanty. The present study was undertaken to explore the phytoplankton flora at Dakshin Rupshi Station of the river Shitalakhsya, Narayanganj, Dhaka. The study was carried out from May 2017 to March 2018 by collecting pelagic plankton samples bimonthly. A total of 53 species under 36 genera were identified, of which 51 species have been illustrated through photomicrographic images and listing. Two species of phytoplankton namely, Pyrobotrys incurva Arnoldi and Phacus ranula Pochmann were identified from the river water but could not be produced here. The recorded algal divisions of phytoplankton are Cyanophyta (6), Chlorophyta (19), Euglenophyta (13), Chrysophyta (13) and Pyrrhophyta (2). The standing crops presented by each division are: 463.5, 428.33, 199.67, 664.33 and 26.25×103 ind/l by Cyanophyta, Chlorophyta, Euglenophyta, Chrysophyta and Pyrrhophyta, respectively. The trend in contributing the number of species is Chlorophyta > Euglenophyta and Chrysophyta > Cyanophyta > Pyrrhophyta. For standing crop, the trend is Chrysophyta > Cyanophyta > Chlorophyta > Euglenophyta > Pyrrhophyta. Pollutant loading from the urban sources actually cuts the penetration of light into the upper part of the river water and thus creating a shrinking environment for the survival of phytoplankton. The present floristic study of phytoplankton of the River Shitalakhsya adds knowledge to the species composition and their systematic position which would be helpful for any further floristic study of phytoplankton on the river ecosystems of Bangladesh. Dhaka Univ. J. Biol. Sci. 31(1): 45-57, 2022 (January)